A demographic and descriptive study on depression status of adolescent population of Ahmedabad city in India - Thakor, Nitin R.; Tolani, Jayshree N.; Pravender (International Journal Of Community Medicine And Public Health, 2023)
Background: Depressive indications and spirituality are prevalent all around the world, but their coherent existence has received moderately minute consideration from majority psychological health experts. This quantitative research examines relationships between spiritual participation and depressive indications or disorders. Religious beliefs and rituals possibly will aid public to deal with improved stressful life conditions, give sense and hope, and encircle unhappy people with an encouraging society. This study aimed to investigate the role that spiritual factors play in inhibiting depression and will lend a hand to determine whether this is a resource or a liability in adult age group. Methods: The present study was carried out in Ahmedabad city in the period from November to December 2022. A total of 400 adults were included in the study, which were selected using multi-stage sampling aged between 18 years to 59 years. Results: The obese adults had significantly higher depression levels. Depression had a negative correlation with spirituality levels. Regression analysis also demonstrated that the spirituality was one of the influencing factors affecting depression. Conclusions: Spirituality is negatively associated with depression.